Symmetry Effects in Photoinduced Electron Transfer in Chlorin‐Quinone Dyads: Adiabatic Suppression in the Marcus Inverted Region. Issue 71 (19th November 2020) - Abel, Yvonne; Vlassiouk, Ivan; Lork, Enno; Smirnov, Sergei; Talipov, Marat R.; Montforts, Franz‐Peter
Abstract: In donor–acceptor dyads undergoing photoinduced electron transfer (PET), a direction or pathway for electron movement is usually dictated by the redox properties and the separation distance between the donor and acceptor subunits, while the effect of symmetry is less recognized. We have designed and synthesized two isomeric donor–acceptor assemblies in which electronic coupling between donor and acceptor is altered by the orbital symmetry control with the reorganization energy and charge transfer exothermicity being kept unchanged. Analysis of the optical absorption and luminescence spectra, supported by the DFT and TD‐DFT calculations, showed that PET in these assemblies corresponds to the Marcus inverted region (MIR) and has larger rate for isomer with weaker electronic coupling. This surprising observation provides the first experimental evidence for theoretically predicted adiabatic suppression of PET in MIR, which unambiguously controlled solely by symmetry. Abstract : Two isomeric donor–acceptor assemblies were designed in which electronic coupling is controlled by the orbital symmetry of constituents, while the free energy of photoinduced electron transfer (PET) is constant. This combined experimental/theoretical study surprisingly showed more efficient PET in the isomer with weaker electronic coupling, thus providing a first experimental validation of adiabatic suppression of PET in the Marcus inverted region.